Temporal pattern of dengue cases in central zone of Shah Alam: a retrospective study from 2013 to 2016 / Muhammad Syukri Rahmat - Rahmat, Muhammad Syukri (2017)
Introduction: The increasing number of dengue occurrence from year to year in this country has raised the urgent need to study on the temporal pattern of the dengue cases. Proper understanding on the temporal pattern is important in order to planning the strategy for controlling the dengue occurrence. Objective: The objective of the study was to identify the temporal pattern of dengue cases in central zone of Shah Alam, Selangor from 2013 to 2016. Methodology: In this study, daily confirmed dengue cases data from 4 years outbreak occurring in central zone of Shah Alam is utilized to compute the corresponding weekly cumulative percentage of total case numbers. Four time series data was being divided into two periods to examine the corresponding weekly cumulative percentages of case numbers for each period. Pearson’s correlation coefficient was calculated to determine the pattern and behavior of the dengue cases occurrence. Result: Three cut-off points produce the most interesting pattern and behaviour and the most different outcome. The result implied that the temporal pattern of dengue cases in 2013 is markedly different when compared to the other three years (2014, 2015 and 2016). It was found that the temporal pattern of dengue cases has changed from 2013 to 2016 as the number of dengue cases in 2013 is high during the end of the year while for the other three years, the number of cases is low during end of the year but slightly high during the first 26 epid week. Conclusion: The outcomes of this study shows that the temporal pattern of dengue cases in the central zone of Shah Alam are differ for the last 4 years of occurrence. However the numbers are still keep increasing from year to year and proper preventive measure should be done quickly to break the chain of the transmission.